Automatic crash detection system for two-wheeled vehicles: design and experimental validation. Issue 5 (2019) - Gelmini, Simone; Strada, Silvia; Tanelli, Mara; Savaresi, Sergio; Tommasi, Claudio De
Abstract: In the insurance telematics context, four-wheeled vehicles are being equipped with e-Boxes installed on the battery, allowing an online monitoring of the vehicle motion thanks to an inertial measurement unit and a GPS unit. The main service that the e-Box enables is the automatic reconstruction of the real crash dynamics, and the detection of potentially dangerous situations, with the subsequent automatic activation of rescue operations, both for driver and passengers and for the vehicle itself. How to design such system for two-wheeled vehicles is far from trivial, as the dynamics of two-wheelers is much different, and so are the ways in which accidents may occur. In this work, a novel crash detection algorithm for two-wheeled vehicles is presented, and its validity is proved against experimental data.